2015
DOI: 10.5194/ars-13-9-2015
|View full text |Cite
|
Sign up to set email alerts
|

Reflexionseigenschaften von Windenergieanlagen im Funkfeld von Funknavigations- und Radarsystemen

Abstract: Abstract. Die hier behandelte Untersuchung befasst sich mit den Störungen des elektrischen Feldes einer Doppler Very High Frequency Omnidirectional Radio Range Navigationsanlage (DVOR) in der Gegenwart von Windenergieanlagen (WEA). Hierfür wird die Feldstärke auf 25 konzentrischen Kreisbahnen, sog. Orbit Flights verschiedener Höhen und mit verschiedenen Radien rund um die DVOR-Anlage numerisch simuliert. Insbesondere werden die Einflüsse diverser Parameter der WEA wie deren Anzahl, Position, Rotorwinkel, Turmh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…As mentioned in the introduction the omnidirectional carrier wave of a DVOR surveillance antenna, consisting of 51 Alford Loop (AL) antennas, is used as the source of the simulation setup. Therefor, according to Sandmann et al (2015), only the center AL antenna of the DVOR model shown in Fig. 3 is fed, whereas the remaining AL antennas are complex-conjugated impedance matched.…”
Section: Simulation Setupmentioning
confidence: 99%
“…As mentioned in the introduction the omnidirectional carrier wave of a DVOR surveillance antenna, consisting of 51 Alford Loop (AL) antennas, is used as the source of the simulation setup. Therefor, according to Sandmann et al (2015), only the center AL antenna of the DVOR model shown in Fig. 3 is fed, whereas the remaining AL antennas are complex-conjugated impedance matched.…”
Section: Simulation Setupmentioning
confidence: 99%